SWOT-analysis of digital maturity of construction participants - Rasputnyi, D.; Koval, O.; Pyliuta, V. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to a comprehensive SWOT analysis of the digital maturity of construction participants. The application of the SWOT methodology, which covers strengths, weaknesses, opportunities and threats, is also relevant to developers, contractors and designers, shedding light on the complex dynamics in each group of participants, after the construction industry experiences a profound digital transformation, The article reveals the strengths of development companies that have begun the process of digital transformation, emphasizing innovative project visualization and financial modeling. The used digital tools enable the developer to make an informed decision, optimizing the evaluation of project invalidity. However, the assessment also acknowledges some weaknesses, such as the limited adoption of Building Information Modeling (BIM), underlining the importance of overcoming the backlog of change to fully utilize digital methodologies. For contractors, the article recognizes their strengths in digital project management and on-site technology integration that improves efficiency and real-time monitoring. However, it highlights the weaknesses of limited BIM integration and skills gaps among the workforce, creating challenges for seamless collaboration and optimal use of tools. The article highlights the strengths of projects in the adoption of design parameters by Ukrainian project organizations and promotion of digital cooperation. However, this does not address current weaknesses such as interoperability issues and skills gaps in sustainable design, emphasizing the need for streamlined workflows and ongoing skills development. The article also talks about ways of growth and possibilities of digitalization for each group of construction participants. Developers are encouraged to invest in data-driven decision making and a collaborative platform, while Contractors are encouraged to explore advanced construction technologies and prioritize a collaborative platform. Designers are offered opportunities for virtual design and construction (VDC) and the integration of Internet of Things (IoT) devices into their design processes, promoting innovation and efficiency. The article also examines existing challenges that construction participants may face. Developers may face threats related to unfair competition and data security issues. Contractors must overcome threats related to competitive pressures and project support, while designers may face challenges such as competitive disadvantage and resistance to Building Information Modeling (BIM) methodologies.